IoT Smart Agriculture for Aquaponics and Maintaining Goat Stall System - Rostam Effendi, Mohammad Kamil; Kassim, Murizah; Arbain Sulaiman, Norakmar; Shahbudin, Shahrani (International Journal of Integrated Engineering, 2020)
This present a project development on smart farm and agriculture. The surge in global population is compelling a shift towards smart farm and agriculture practices. This coupled with the diminishing natural resources increase in unpredictable weather conditions makes food security a major concern for most countries. As a result, the use of internet of things (IoT) and data analytics (DA) are employed to enhance the operational efficiency and productivity in the farm and agriculture sector. The objective is to design a prototype that used internet of things in the farm and agriculture. Next is to have a monitoring and controlling or automation system that will benefits the farmer. Then collect all the data to be analyses on the rainfall, temperature, humidity and light intensity. The methodology comprised of hardware, software, programming, sensors such as water sensor, light depending resistor sensor, temperature and humidity sensor and weight sensor for collected data. Result presents a prototype on aquaponics and goat stall that implement the concepts of internet of things for monitoring, controlling or automation system while data analytics is presented from all the sensors. Analytic data on the temperature, light intensity, humidity and rainfall rate are analyzed. Surrounding temperature are important for both plant and fish because if it too hot, they can die easily. While optimum light is needed by the plant for their photosynthesis process. Thus, by monitoring and collecting these parameters, data can be used for analyzing purpose. This project can benefits agriculture and farm sector. Prototype also can be used for small size like at the backyard or balcony of the house for person that likes gardening.